Features of Karakalpak Folk Rituals Songs (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes the features of the national identity of the Karakalpak people on the example of Karakalpak folklore heritage. The article is based on the analysis of songs that have developed due to certain customs and traditions of the people. The content and idea of ritual songs, which from all eternity have been integral part of the life of the Karakalpaks, are revealed. Lullabies, wedding, mourning ritual songs, their performance, originality is the object of study. All these features are supported by the given extracts from the songs.